Exploring the managerial challenges in infrastructure projects: A statistical analysis - Lamichhane, Basu Dev; Giri, Om Prakash; Khadka, Suman; Htet, Arkar (Edelweiss Applied Science and Technology, 2025)
The main objective of this study is to examine the managerial challenges of road construction projects in Nepal. Improved road infrastructure is key to socio-economic progress. Identifying challenges hindering efficient road infrastructure development in rapidly growing countries like Nepal is essential for implementing improvement measures and promoting sustainable economic development. The study employs a mixed-methods approach, integrating qualitative interviews, quantitative analysis, and on-site observations. Surveys with contractors, clients, and consulting engineers, along with interviews with project managers, utilize a Likert five-point scale questionnaire, analyzed via the Relative Importance Index (RII), to comprehensively assess road construction challenges. The findings identify challenges, with stakeholders unanimously ranking poor project management, improper use of advance payments by contractor entrepreneurs, and financial constraints as the top three critical factors. The study outlines eleven effects of these challenges on road projects, emphasizing time overruns, scope changes, and cost escalations. Addressing these challenges and adopting proposed measures can enhance project outcomes, optimize resource allocation, and expedite construction timelines. Policymakers, practitioners, regulators, managers, and stakeholders are urged to implement these recommendations to mitigate obstacles and strengthen the effectiveness of road-building efforts in Nepal, fostering sustainable economic development and national resilience.